2022
DOI: 10.3389/fgene.2022.934154
|View full text |Cite
|
Sign up to set email alerts
|

Identification of programmed cell death-related gene signature and associated regulatory axis in cerebral ischemia/reperfusion injury

Abstract: Background: Numerous studies have suggested that programmed cell death (PCD) pathways play vital roles in cerebral ischemia/reperfusion (I/R) injury. However, the specific mechanisms underlying cell death during cerebral I/R injury have yet to be completely clarified. There is thus a need to identify the PCD-related gene signatures and the associated regulatory axes in cerebral I/R injury, which should provide novel therapeutic targets against cerebral I/R injury.Methods: We analyzed transcriptome signatures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 114 publications
0
8
0
1
Order By: Relevance
“…Six candidate genes (IL2, NOC2L, LEP, BIRC2, DLD, and CTSL) were identi ed, four of which have been previously studied in association with IS, while NOC2L and BIRC2 are the rst to appear in IS-related studies. IL possesses vital biological properties that include maintaining long-term T cell proliferation and differentiation in vitro, increasing B cell proliferation and differentiation, enhancing NK cell killing activity, and inducing the production of lymphokine-activating factors (33). The IL-2/IL-2 antibody complex (IL-2/IL-2Ab) regulates the number of regulatory T cells (Treg) in vivo, which may improve the prognosis of ischemic stroke (34).…”
Section: Discussionmentioning
confidence: 99%
“…Six candidate genes (IL2, NOC2L, LEP, BIRC2, DLD, and CTSL) were identi ed, four of which have been previously studied in association with IS, while NOC2L and BIRC2 are the rst to appear in IS-related studies. IL possesses vital biological properties that include maintaining long-term T cell proliferation and differentiation in vitro, increasing B cell proliferation and differentiation, enhancing NK cell killing activity, and inducing the production of lymphokine-activating factors (33). The IL-2/IL-2 antibody complex (IL-2/IL-2Ab) regulates the number of regulatory T cells (Treg) in vivo, which may improve the prognosis of ischemic stroke (34).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Recently, the role of lncRNAs in the diagnosis and treatment of liver diseases has also been recognized. 33,34 It has also been reported that lncRNAs participate in gene regulation during ischemia-reperfusion injury of important organs such as the brain 35,36 and the heart. 37 Nevertheless, research on lncRNAs expression profiles in liver transplantation is still limited and is mainly derived from animal or in vitro models of liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of lncRNAs in the diagnosis and treatment of liver diseases has also been recognized 33,34 . It has also been reported that lncRNAs participate in gene regulation during ischemia–reperfusion injury of important organs such as the brain 35,36 and the heart 37 …”
Section: Discussionmentioning
confidence: 99%
“…Initially, we collected 268 programmed cell death genes (PCD genes) from existing literature sources [ 24 , 25 ]. Using scRNA-seq datasets, we identified 3,000 cell Differential genes (cellDiffgenes) intersecting with PCD genes to obtain our target gene.…”
Section: Methodsmentioning
confidence: 99%